Application of the Green Function Method for Calculating the Spatial Distribution of Electrons in the Finite System. (December 2020) - Yu Igashov, S; Blinnikov, S I; Kuratov, S E; Shidlovski, D S
Abstract: The paper presents a numerical implementation of the Green's function method for calculating the spatial distribution of the macroscopic number of free electrons in a finite system. The obtained results are compared with the results obtained by direct summation of the wave functions. The quantitative coincidence is demonstrated.